PROSPECTS FOR USING TOCILIZUMAB IN SYSTEMIC SCLEROSIS - L. P. Ananyeva (Научно-практическая ревматология)
Interleukin 6 (IL-6) is one of the key cytokines that are involved in inflammation and that has pleiotropic properties. Diverse effects of IL-6 result from the transmission of an intracellular signal in two ways: via direct binding to a membrane receptor having a molecular mass of 80 kDA (a classical way) or absorption of the IL-6 complex with its soluble receptor on another transmembrane receptor – gp-130 (trans-signaling). Different signaling pathways lead to various consequences. The classical way of signal transmission activates mainly protective and regenerative processes; trans-signaling has a proinflammatory potential. The review gives schemes of signal stimuli and shows that IL-6 and its receptors are a dynamic intricately organized regulatory system that can adapt to stress-induced homeostatic changes. It considers in detail evidence suggesting the effect of IL-6 on the development and maintenance of a number of systemic sclerosis (SS)-specific pathogenetic disorders, such as the activation of the endothelium, the development and maintenance of inflammation, and excessive deposition of extracellular matrix components in tissues. Endothelial cell activation during trans-signaling gives rise to an enhanced adhesion molecule expression, chemokine release, and further production of IL-6. Excessive secretion of the latter may initiate a fibrosing process and favor the further development of pathologicalconditions. Autoimmune disorders theoretically associated with IL-6 overproduction occur in SS. Elevated blood IL-6 concentrations in SS are related to disease clinical parameters, such as activity, severity, worse prognosis, and reduced survival. Taken together, the data presented suggest that IL-6 blocking may have a therapeutic potential in SS. The first clinical data on successfully using the IL-6 receptor antagonist tocilizumab to treat SS are given.